2013
DOI: 10.1002/eqe.2363
|View full text |Cite
|
Sign up to set email alerts
|

Closed‐form aftershock reliability of damage‐cumulating elastic‐perfectly‐plastic systems

Abstract: Major earthquakes (i.e., mainshocks) typically trigger a sequence of lower magnitude events clustered both in time and space. Recent advances of seismic hazard analysis stochastically model aftershock occurrence (given the main event) as a nonhomogeneous Poisson process with rate that decays in time as a negative power law. Risk management in the post-event emergency phase has to deal with this short-term seismicity. In fact, because the structural systems of interest might have suffered some damage in the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 22 publications
(41 reference statements)
1
35
0
Order By: Relevance
“…It is shown that the probability increase due to the main shock is the largest in the presented case studies, but it is only a fraction of the cumulative probability of exceedance of a damage state throughout the aftershock sequences. The probability of damage state exceedance in the numerical results for the case studies of the aftershock sequences of the Thessaloniki (1978) and the Northridge (1994) follows a similar trend to the failure probability during the aftershock sequence period as estimated by Iervolino et al [5]. Moreover, the assumption that period elongation of ΔΤ = 60 % corresponds to a state near collapse is in agreement with the empirical estimations by Katsanos and Sextos [10].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is shown that the probability increase due to the main shock is the largest in the presented case studies, but it is only a fraction of the cumulative probability of exceedance of a damage state throughout the aftershock sequences. The probability of damage state exceedance in the numerical results for the case studies of the aftershock sequences of the Thessaloniki (1978) and the Northridge (1994) follows a similar trend to the failure probability during the aftershock sequence period as estimated by Iervolino et al [5]. Moreover, the assumption that period elongation of ΔΤ = 60 % corresponds to a state near collapse is in agreement with the empirical estimations by Katsanos and Sextos [10].…”
Section: Discussionsupporting
confidence: 86%
“…Iervolino et al [5] focused on earthquake clusters (aftershock sequences) and developed a probabilistic damage accumulation model for elastic-perfectly plastic single-degree-of-freedom (SDOF) structures and estimated the failure probability as an increasing function of time. Repeated earthquakes and the subsequent damage accumulation may lead to an increased inelastic displacement demand of SDOF systems and an increased ratio of the inelastic displacement to the maximum displacement of the elastic system [6].…”
Section: Introductionmentioning
confidence: 99%
“…The strong aftershocks that occur after a large subduction earthquake will adversely affect recovery activities [29][30][31]. For example, the gas, water, and electricity supply were disconnected over a wide area owing to an aftershock with a magnitude of 7.2 on 07 April, 2011, nearly a month after the Tohoku earthquake.…”
Section: Aftershock Hazard Map For Recovery Activitiesmentioning
confidence: 99%
“…Some recent examples in the literature address the increase in a building's vulnerability to ground shaking due to increased structural load following volcanic ash fall or heavy snowfall or after being subjected to a blast (Lee and Rosowsky 2006;Zuccaro et al, 2008;Asprone et al, 2010;Selva 2013;). Another well-known situation is the increased vulnerability of structures to successive shaking during an earthquake cluster or sequence Iervolino et al, 2014).…”
Section: Time-variant Vulnerabilitymentioning
confidence: 99%